A biodegradable composite material and a method for preparing the same
By blending PHBH, PBAT and PLA and adding a compatibilizer, the prepared composite material solves the problem of poor mechanical properties of PHBH, achieves improved mechanical properties and biodegradability, and is suitable for disposable tableware and packaging materials.
Patent Information
- Application Number
- CN202510086040.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-10-17
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The existing bio-based material poly(3-hydroxybutyrate-3-hydroxyhexanoate) (PHBH) has problems such as poor mechanical properties and narrow processing window. Polylactic acid (PLA) is very brittle and it is difficult to have both good mechanical properties and biodegradability.
Composite materials were prepared by melt blending using PHBH, PBAT and PLA as main raw materials, adding PLA-g-MAH or epoxy chain extender REC as compatibilizer, and improving the compatibility and mechanical properties of each component.
The prepared composite material has significantly improved mechanical properties and good biodegradability, making it suitable for disposable tableware and packaging materials, and in line with the requirements of green and low-carbon development.
Smart Images

Figure BDA0005250162770000061
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of biodegradable materials, and particularly relates to a biodegradable composite material and a preparation method thereof. BACKGROUND
[0002] In recent years, bio-based materials have attracted widespread attention due to their sustainable and environmentally friendly characteristics that are different from petroleum-based materials. As two major representative polymers in biodegradable polymers, polyhydroxyalkanoate (PHA) and polylactic acid (PLA) have gradually become the research and development hotspot. PHA is a bio-based material, which has excellent biodegradability and biocompatibility. Poly(3-hydroxybutyrate-3-hydroxyhexanoate) (PHBH) is a member of the PHA family, which has good elasticity and plasticity, but has the shortcomings of poor mechanical properties (low elongation at break, tensile strength and tensile elastic modulus) and narrow processing window, thereby limiting its wide application. PLA is a thermoplastic degradable aliphatic polyester, which has good transparency, mechanical properties, thermal stability and biodegradability, but has high brittleness. Therefore, there is an urgent need for a biodegradable composite material with good mechanical properties and biodegradability, which has positive significance for green, low-carbon and sustainable development. SUMMARY
[0003] The purpose of the application is to provide a biodegradable composite material and a preparation method thereof, so as to solve the problems existing in the prior art and improve the mechanical properties of biodegradable materials.
[0004] To achieve the above purpose, the application provides the following solutions.
[0005] One of the technical solutions of the application is a biodegradable composite material, wherein the raw materials include 50-60 parts of PHBH, 30-40 parts of PBAT (polybutylene terephthalate-adipate-dimethyl ester), 10-20 parts of PLA and 1-4 parts of a compatibilizer, by mass fraction; the compatibilizer is a PLA-g-MAH graft copolymer or an epoxy chain extender REC; and the total amount of the PHBH, the PBAT and the PLA is 100 parts.
[0006] The application utilizes the advantages of high strength and hardness and processability of PLA, and blends it with PHBH to improve the mechanical properties of PHBH, PBAT is a kind of environment-friendly biodegradable polymer material, which has good ductility and elongation at break, and the use of PHBH, PLA and PBAT can play a certain role of interface active agent, improve the compatibility of PHBH and PLA, and PBAT can also improve the performance of aliphatic polyester, and then improve the mechanical properties and processability of the material. The application utilizes the certain complementarity of PHBH, PLA and PBAT in performance, and uses PHBH, PBAT and PLA as the main raw materials of biodegradable composite material, and blends them to improve the performance of each other. In order to further improve the compatibility between the components, the application further selects PLA-g-MAH or epoxy chain extender REC as a compatibilizer, wherein the PLA-g-MAH is a graft copolymer of PLA and MAH (maleic anhydride), and the anhydride group can react with the terminal hydroxyl group of PHBH, PLA and PBAT, and play a role of chemical compatibilization. The epoxy chain extender REC is a copolymer of glycidyl methacrylate and styrene, which has epoxy groups, and can react with the terminal hydroxyl group and the terminal carboxyl group in PHBH, PLA and PBAT, enhance the combination between the phase interfaces, and then improve the compatibility between the components, so that the prepared biodegradable composite material has good mechanical properties and biodegradability.
[0007] The application can obtain better mechanical properties by controlling the amount of PHBH, PBAT and PLA as PHBH> PBAT> PLA, and has good biodegradability.
[0008] The amount of the compatibilizer should not be too high, otherwise it will affect the mechanical properties, and the elongation at break and impact strength of the product will decrease. When the addition amount of REC is too much, agglomeration phenomenon occurs, the chain extension efficiency decreases, and the performance of the composite material is affected.
[0009] Preferably, the raw materials include 50 parts of PHBH, 40 parts of PBAT, 10 parts of PLA and 2 parts of compatibilizer.
[0010] Preferably, the PLA-g-MAH graft copolymer is prepared by melt mixing with PLA, MAH and DCP (dicumyl peroxide) as raw materials;
[0011] Preferably, the raw materials of the PLA-g-MAH are 98 parts of PLA, 2 parts of MAH and 0.4 parts of DCP.
[0012] Preferably, the temperature of the melt mixing is 175-185 DEG C.
[0013] Preferably, the epoxy chain extender REC is obtained by suspension polymerization of glycidyl methacrylate and styrene.
[0014] Preferably, the PHBH has a molecular weight of 6*10 5 , the PBAT has a weight average molecular weight of 1.26*10 5 g / mol, and the PLA has a weight average molecular weight of 2.23*10 5 g / mol.
[0015] The second technical solution of the present application, the preparation method of the above biodegradable composite material, comprises the following steps:
[0016] After the PHBH, the PLA, the PBAT and the compatibilizer are fully mixed, they are added into a double-screw extrusion granulator, and are melt-extruded and granulated to obtain the biodegradable composite material.
[0017] Preferably, the melt-extrusion temperature is 145-170 DEG C, the main screw rotation speed is 60-65 r / s, and the feeding rotation speed is 4-6 r / s.
[0018] Preferably, the temperature setting of the 1-9 zones of the double-screw extrusion granulator is 150 DEG C, 152 DEG C, 159 DEG C, 159 DEG C, 165 DEG C, 165 DEG C, 160 DEG C, 160 DEG C and 153 DEG C respectively.
[0019] The present application adopts a melt blending method to prepare a PHBH / PLA / PBAT composite material with excellent mechanical properties, and the process is simple and easy to operate, and is suitable for large-scale production.
[0020] The third technical solution of the present application, the application of the above biodegradable composite material in preparing disposable tableware and / or packaging materials.
[0021] The present application has the following technical effects:
[0022] The present application uses PHBH, PBAT and PLA as the main raw materials of the biodegradable composite material, blends and modifies them to improve their respective properties, adds a compatibilizer into the raw materials, significantly improves the mechanical properties of the prepared composite material, and has good biodegradability. The obtained PHBH / PBAT / PLA composite material is suitable for making plastic products such as disposable tableware and packaging materials through molding processes such as mold pressing, injection molding and blow molding, has the advantages of non-toxicity and environmental friendliness, and has positive significance for green, low-carbon and sustainable development. DETAILED DESCRIPTION
[0023] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0024] It should be understood that the terms described herein are intended only to describe particular embodiments and are not intended to limit the present invention. In addition, for numerical ranges herein, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value within any stated value or stated range, and each smaller range between any other stated value or intermediate value within the stated range, is also encompassed within the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded within the scope.
[0025] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of any conflict with any incorporated document, the contents of this specification shall prevail.
[0026] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments described herein without departing from the scope or spirit of the invention. Other embodiments will be apparent to those skilled in the art from the description of the invention. The description and examples are intended to be illustrative only.
[0027] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0028] In the following embodiments of the present invention:
[0029] The PHBH used was purchased from Kaneka (Kaneka Chemical) Company of Japan, X131A, with a molecular weight of 6×10 5 , HH content is 6%;
[0030] The PLA used was purchased from Natureworks 4032D, with a weight average molecular weight of 2.23×10 5 g / mol;
[0031] The PBAT used was purchased from 1903E of Hangzhou Xinfu Pharmaceutical Co., Ltd., Zhejiang Province, with a weight average molecular weight of 1.26×10 5 g / mol;
[0032] MAH was purchased from National Pharmaceutical Group Chemical Reagent Co., Ltd., molecular weight 98.06, density 1.32 g / mL, melting point 51-56℃;
[0033] DCP was purchased from Aladdin Reagent (Shanghai) Co., Ltd. D1324007, molecular weight 270.37, density 1.56 g / mL, melting point 39-41℃;
[0034] The epoxy chain extender REC used was 6000E from Hangzhou Xusheng New Material Technology Co., Ltd., which was obtained by suspension polymerization of glycidyl methacrylate and styrene.
[0035] The polylactic acid grafted maleic anhydride (PLA-g-MAH) used was obtained by melt mixing 98 parts of PLA, 2 parts of MAH and 0.4 parts of DCP at a temperature of 180℃, and then crushing the obtained graft product in a crusher. The graft product was placed in a beaker, and chloroform was added to the beaker to completely dissolve the graft product. Methanol was gradually added dropwise to the beaker, and the beaker was left to stand at room temperature, then the supernatant was poured out, and the precipitate was washed with an appropriate amount of methanol several times. The obtained graft product was filtered, and the pure graft product was dried in a vacuum oven at 80℃ for 12h.
[0036] Example 1
[0037] The following weight parts of raw materials were used to prepare the biodegradable composite material:
[0038] PHBH 50 parts, PBAT 40 parts, PLA 10 parts, PLA-g-MAH 1 part.
[0039] Preparation method: the above raw materials were weighed according to the weight parts, added to a twin-screw extruder, and then extruded and granulated after melt blending. The temperature settings of the twin-screw extruder 1-9 zones were 150℃, 152℃, 159℃, 159℃, 165℃, 165℃, 160℃, 160℃, and 153℃, respectively. The main screw rotation speed was 65r / s, and the feeding rotation speed was 6r / s.
[0040] Example 2
[0041] The same as example 1, except that the following weight parts of raw materials were used to prepare the biodegradable composite material:
[0042] PHBH 50 parts, PBAT 40 parts, PLA 10 parts, PLA-g-MAH 2 parts.
[0043] Example 3
[0044] The same as example 1, except that the following weight parts of raw materials were used to prepare the biodegradable composite material:
[0045] PHBH 50 parts, PBAT 40 parts, PLA 10 parts, PLA-g-MAH 4 parts.
[0046] Example 4
[0047] The same as Example 1, except that the biodegradable composite material was prepared using the following raw materials in parts by weight:
[0048] PHBH 50 parts, PBAT 40 parts, PLA 10 parts, REC 1 part.
[0049] Example 5
[0050] The same as Example 1, except that the biodegradable composite material was prepared using the following raw materials in parts by weight:
[0051] PHBH 50 parts, PBAT 40 parts, PLA 10 parts, REC 2 parts.
[0052] Example 6
[0053] The same as Example 1, except that the biodegradable composite material was prepared using the following raw materials in parts by weight:
[0054] PHBH 50 parts, PBAT 40 parts, PLA 10 parts, REC 4 parts.
[0055] Comparative Example 1
[0056] The same as Example 1, except that the raw material compatibilizer PLA-g-MAH was omitted.
[0057] Comparative Example 2
[0058] The same as Example 1, except that 1 part of PLA-g-MAH was replaced with 4 parts of PEO (polyethylene oxide, source: China Pharmaceutical Group Chemical Reagents Co., Ltd. U1546853).
[0059] Comparative Example 3
[0060] The same as Example 1, except that 1 part of PLA-g-MAH was replaced with 4 parts of E-GMA (ethylene-glycidyl methacrylate copolymer, source: Sumitomo Chemical Co., Ltd.).
[0061] Comparative Example 4
[0062] The same as Example 1, except that the biodegradable composite material was prepared using the following raw materials in parts by weight:
[0063] PHBH 33 parts, PBAT 33 parts, PLA 33 parts, PLA-g-MAH 4 parts.
[0064] Comparative Example 5
[0065] The same as example 1, except that the biodegradable composite was prepared using the following weight parts of raw materials:
[0066] PHBH 33 parts, PBAT 33 parts, PLA 33 parts, REC 4 parts.
[0067] Comparative Example 6
[0068] The same as example 1, except that the biodegradable composite was prepared using the following weight parts of raw materials:
[0069] PHBH 20 parts, PBAT 40 parts, PLA 40 parts, PLA-g-MAH 4 parts.
[0070] Comparative Example 7
[0071] The same as example 1, except that the biodegradable composite was prepared using the following weight parts of raw materials:
[0072] PHBH 20 parts, PBAT 40 parts, PLA 40 parts, REC 4 parts.
[0073] Comparative Example 8
[0074] The same as example 1, except that the biodegradable composite was prepared using the following weight parts of raw materials:
[0075] PHBH 50 parts, PBAT 40 parts, PLA 10 parts, PLA-g-MAH 10 parts.
[0076] Comparative Example 9
[0077] The same as example 1, except that the biodegradable composite was prepared using the following weight parts of raw materials:
[0078] PHBH 50 parts, PBAT 50 parts, PLA-g-MAH 4 parts.
[0079] Comparative Example 10
[0080] The same as example 1, except that the biodegradable composite was prepared using the following weight parts of raw materials:
[0081] PHBH 50 parts, PLA 50 parts, PLA-g-MAH 4 parts.
[0082] Comparative Example 11
[0083] The same as example 1, except that the biodegradable composite was prepared using the following weight parts of raw materials:
[0084] PLA 50 parts, PBAT 50 parts, PLA-g-MAH 4 parts.
[0085] Test Example
[0086] The products prepared in the examples and comparative examples were subjected to performance tests, and the specific test methods were as follows:
[0087] Mechanical property test:
[0088] (1) The sample was made into a dumbbell-shaped sample (for tensile property test), and was placed in a laboratory environment for 48 h. According to the requirements of GB / T 1040.2-2006, an electronic universal testing machine was used to test the tensile property, the tensile speed was 10 mm / min, and 5 samples were determined for each group to take the average value.
[0089] (2) The sample was made into a rectangular sample (for impact property test), and was placed in a laboratory environment for 48 h. According to the requirements of GB / T 1843-2008, an electronic cantilever beam impact tester was used to perform impact test, and 5 samples were determined for each group to take the average value.
[0090] Thermal stability test: about 5 mg of sample was taken, and a thermal gravimetric analyzer was used to rapidly heat from room temperature to 600℃ at a heating rate of 10℃ / min in a nitrogen atmosphere. The temperature at which the sample decomposed by 5% was taken as the initial decomposition temperature.
[0091] Degradation property test: a hydraulic machine was used to press the sample into a film, and then according to the requirements of GB / T 19277.1-2011, the 180d biodegradation percentage was determined.
[0092] The experimental results are shown in Table 1.
[0093] Table 1
[0094]
[0095] As can be seen from Table 1, the mechanical properties of the biodegradable composite material of PHBH / PBAT / PLA prepared by adding the compatibilizer are good. Compared with the composite material without adding the compatibilizer, the mechanical properties of the composite material adding 1-4 parts of PLA-g-MAH are more excellent. Since the acid anhydride groups in PLA-g-MAH can react with the terminal hydroxyl groups of PHBH, PLA and PBAT to form a crosslinked structure, the compatibility between the components is improved, thereby the tensile strength and impact strength of the composite material are improved. In addition, the biodegradable composite material of PHBH / PBAT / PLA adding the compatibilizer all meets the requirements of GB / T 41010-2021 on the relative biodegradation rate of degradable plastics. When the compatibilizer is E-GMA or PEO, the mechanical properties of the composite material are decreased due to the poor compatibility between the components; when the ratio of PHBH, PBAT and PLA is not within the range defined in the application, especially when the content of PLA increases, the toughness of the composite material decreases; when the content of PHBH decreases, the impact performance of the composite material decreases, thereby the performance of the product is affected.
[0096] The above-described embodiments are only to describe the preferred modes of the present application, and do not limit the scope of the present application. Without departing from the design spirit of the present application, various modifications and improvements to the technical solutions of the present application made by those skilled in the art shall fall within the protection scope defined by the claims of the present application.
Claims
1. A biodegradable composite material for preparing disposable tableware or packaging materials, characterized in that: Calculated by mass, the raw materials include: 50 parts PHBH, 40 parts PBAT, 10 parts PLA and 2 parts compatibilizer; The compatibilizer is a PLA-g-MAH graft copolymer, and the specific steps are as follows: 98 parts of PLA, 2 parts of MAH and 0.4 parts of DCP are melt-kneaded at a temperature of 180° C., and the obtained graft product is placed in a crusher for crushing; the graft product is placed in a beaker, chloroform is added to the beaker to completely dissolve the graft product, methanol is gradually added dropwise to the beaker, the beaker is allowed to stand at room temperature, and then the supernatant liquid is poured out, and the precipitate is washed with an appropriate amount of methanol multiple times; the obtained graft product is filtered to separate the graft product, and the pure graft product is placed in a vacuum oven at 80° C. and dried for 12 hours; The molecular weight of PHBH is 6×10 5 , HH content is 6%, the PBAT weight average molecular weight is 1.26×10 5 g / mol, the weight average molecular weight of PLA is 2.23×10 5 g / mol; The method for preparing the biodegradable composite material comprises the following steps: After fully mixing PHBH, PLA, PBAT and a compatibilizer, the mixture is added to a twin-screw extruder and granulated, and melt-extruded and granulated to obtain the biodegradable composite material; The melt extrusion temperature is 145-170°C; and / or the main screw speed is 60-65r / s, and the feeding speed is 4-6r / s; The temperature settings of the twin-screw extruder granulator in zones 1-9 are: 150°C, 152°C, 159°C, 159°C, 165°C, 165°C, 160°C, 160°C, and 153°C respectively.
2. Use of the biodegradable composite material according to claim 1 in preparing disposable tableware or packaging materials.
Citation Information
Patent Citations
Functional biodegradable mulching film, and preparation method and application thereof
CN107266876A
Compatibilizer for increasing PLA / PBAT compatibility and high-filling full-biodegradable composite material
CN114805697A